433 MHz implantable wireless stimulation of spinal nerves - Carmo, João Paulo Pereira (2010)
This paper presents a implantable wireless microsystem concept for operation in the 433 MHz ISM band. The proposed microsystem is composed by two independent subsystems: the electrostimulation and the radio frequency (RF) subsystems. The electrostimulation part is a silicon box with groves to pass the nerves to be stimulated. The cover of the silicon box contains electrodes for electrical contacting with the nerves. Wafer level packaging (WLP) techniques will allow the joining of the RF and the electrostimulation subsystems. The target of this implantable microsystem is for RF reception at 433 MHz of user commands to activate the micturition function and the erection (on males) patients. The expected microsystem area will be of 5x5mm2.